Comparison of [11C]UCB-J and [18F]FDG PET in Alzheimer's disease: A tracer kinetic modeling study. Issue 9 (September 2021) - Chen, Ming-Kai; Mecca, Adam P; Naganawa, Mika; Gallezot, Jean-Dominique; Toyonaga, Takuya; Mondal, Jayanta; Finnema, Sjoerd J; Lin, Shu-fei; O'Dell, Ryan S; McDonald, Julia W; Michalak, Hannah R; Vander Wyk, Brent; et al.
[ 11 C]UCB-J PET for synaptic vesicle glycoprotein 2 A (SV2A) has been proposed as a suitable marker for synaptic density in Alzheimer's disease (AD). We compared [ 11 C]UCB-J binding for synaptic density and [ 18 F]FDG uptake for metabolism (correlated with neuronal activity) in 14 AD and 11 cognitively normal (CN) participants. We assessed both absolute and relative outcome measures in brain regions of interest, i.e., K 1 or R 1 for [ 11 C]UCB-J perfusion, V T (volume of distribution) or DVR to cerebellum for [ 11 C]UCB-J binding to SV2A; and K i or K i R to cerebellum for [ 18 F]FDG metabolism. [ 11 C]UCB-J binding and [ 18 F]FDG metabolism showed a similar magnitude of reduction in the medial temporal lobe of AD –compared to CN participants. However, the magnitude of reduction of [ 11 C]UCB-J binding in neocortical regions was less than that observed with [ 18 F]FDG metabolism. Inter-tracer correlations were also higher in the medial temporal regions between synaptic density and metabolism, with lower correlations in neocortical regions. [ 11 C]UCB-J perfusion showed a similar pattern to [ 18 F]FDG metabolism, with high inter-tracer regional correlations. In summary, we conducted the first in vivo PET imaging of synaptic density and metabolism in the same AD participants and reported a concordant reduction in medial temporal regions but a discordant reduction in neocortical regions.